Odpowiedź :
Odpowiedź:
a) 4x - 3 = 3x + 5
4x - 3x = 5 + 3
x = 8
b) 0,4x = 2,1 - 0,3x
0,4x + 0,3x = 2,1
0,7x = 2,1
x = 3
c) x - 6 = [tex]\frac{1}{2}[/tex] x - 4
2x - 12 = x - 8
2x - x = -8 + 12
x = 4
d) [tex]\frac{4x+7}{2}[/tex] - [tex]\frac{5x-1}{6}[/tex] = x + 5
3( 4x + 7) - (5x - 1) = 6x + 30
12x + 21 - 5x + 1 = 6x +30
7x + 22 = 6x + 30
7x - 6x = 30 - 22
x = 8
e) (4 - 5x)(2+x) = -(4+5[tex]x^{2}[/tex])
8 + 4x - 10x - 5[tex]x^{2}[/tex] = -4 - 5[tex]x^{2}[/tex]
8 - 6x - 5[tex]x^{2}[/tex] = -4 - 5[tex]x^{2}[/tex]
8 - 6x = -4
-6x = -4 - 8
-6x = -12
x = 2
Szczegółowe wyjaśnienie: